2020
DOI: 10.2147/opth.s249261
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outcomes of Combined iStent Trabecular Micro-Bypass and Cataract Surgery for the Treatment of Open-Angle Glaucoma in a Saudi Population</p>

Abstract: Purpose: To assess the effectiveness and safety of a single iStent trabecular micro-bypass stent implantation in combination with cataract surgery in lowering the intra ocular pressure (IOP) and number of anti-glaucoma medications in Saudi patients with open-angle glaucoma (OAG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A substantial number of studies have demonstrated significant long-term IOP reduction and medication reduction following the implantation of the iStent. [11][12][13][14][15][16] Our previous study 13 was focused on physiology of aqueous outflow and was intended to confirm the conclusions of work of Batista et al 17 Current manuscript is a typical clinic research, and similar to recent population studies [18][19][20] its aim is to confirm the results of iStent implantation combined with a cataract surgery taking into consideration a Caucasian Polish population.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A substantial number of studies have demonstrated significant long-term IOP reduction and medication reduction following the implantation of the iStent. [11][12][13][14][15][16] Our previous study 13 was focused on physiology of aqueous outflow and was intended to confirm the conclusions of work of Batista et al 17 Current manuscript is a typical clinic research, and similar to recent population studies [18][19][20] its aim is to confirm the results of iStent implantation combined with a cataract surgery taking into consideration a Caucasian Polish population.…”
Section: Introductionmentioning
confidence: 78%
“…Recently Al Habash and Khan 18 released interventional case series on 33 Arabic patients. The mean baseline IOP was 17.47 ± 5.44 mmHg and the mean number of IOP lowering medication was 2.69 ± 0.92.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the most common complication of penetrating canaloplasty is a transient IOP elevation (37.8% > 25 mmHg and 26.7% > 30 mmHg) after the surgery, usually within the first month. This phenomenon frequently occurs in non-penetrating surgeries, like canaloplasty (3% > 30 mmHg to 30% > 25 mmHg) (Brusini, 2014;Grieshaber et al 2010;Matlach et al 2015;Grieshaber et al 2017a) and iStent implantation (10.1%-21%) (Arriola-Villalobos et al 2012;Voskanyan et al 2014;Al Habash et al 2020). Early transient IOP elevation may be due to residual viscoelastic agent, blood and exudative materials in Schlemm's canal during and after the surgery, while a relatively persistent elevated IOP may be related to the collapse of collecting channels secondary to long-term IOP elevation and inadequate aqueous outflow in PACG patients (Johnstone et al 1973;Allingham et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The first-generation iStent trabecular micro-bypass stent (Glaukos, San Clemente, CA, USA) was designed to restore the natural physiological outflow of aqueous humor through the trabecular meshwork into the Schlemm’s canal. Due to its efficacy and good safety profile, this titanium microstent is increasingly being used during cataract phacoemulsification in patients with coexisting mild-to-moderate glaucoma [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Previous studies on the effect of iStent on the corneal endothelial status showed that one year after combined phacoemulsification-iStent surgery, the CECL ranged from 13.2% to 14.6% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effect of iStent on the corneal endothelial status showed that one year after combined phacoemulsification-iStent surgery, the CECL ranged from 13.2% to 14.6% [ 21 ]. The 2-year follow-up showed that the ECD reduction was comparable between eyes with glaucoma in which only phacoemulsification was performed and those in which combined phacoemulsification and iStent surgery were performed, being 12.3% and 13.1%, respectively [ 22 ].…”
Section: Introductionmentioning
confidence: 99%